Determinant of Internet Financial Reporting Disclosure - Devi Narulitasari; Rosalina Zafira (Islamic Accounting Journal, 2021)
So far, internet financial reporting is still a voluntary disclosure. This study aims to determine the effect of local government age, local government size, and audit opinion on internet financial reporting in Java.The population of this study is the Regency or City Government on the island of Java, Indonesia, which consists of 85 regencies and 34 cities. After using purposive sampling, a sample of 136 data was obtained, consisting of 52 regencies and 16 cities during the reporting period from 2018 to 2019. This type of research is quantitative research. The analytical tool used is by using logistic regression. The theory used in this research is Legitimacy theory and agency theory.The results of this study indicate that the disclosure of Inernet Financial Reporting to local governments on the island of Java is 43,38%. The local government age variabel has a significant positive effect on internet financial reporting, while the size of the local government has no significant effect on internet financial reporting, as well as audit opinion has no significant effect on internet financial reporting. It is hoped that local governments can improve internet financial reporting to provide sufficient and adequate financial information to the public. In addition, as a form of transparency and accountability for financial management and local government performance. Keywords: Internet Financial Reporting, Regional Financial Reports, Age of Local Government, Size of Local Government, Audit Opinion.